Organic Matter Causes Chemical Pollutant Dissipation Along With Adsorption and Microbial Degradation - Harju, A. Vilhelmiina; Närhi, Ilkka; Mattsson, Marja; Kerminen, Kaisa; Kontro, Merja H. (Frontiers in Environmental Science, 2021)
Views on the entry of organic pollutants into the organic matter (OM) decaying process are divergent, and in part poorly understood. To clarify these interactions, pesticide dissipation was monitored in organic and mineral soils not adapted to contaminants for 241 days; in groundwater sediment slurries adapted to pesticides for 399 days; and in their sterilized counterparts with and without peat (5%) or compost-peat-sand (CPS, 15%) mixture addition. The results showed that simazine, atrazine and terbuthylazine (not sediment slurries) were chemically dissipated in the organic soil, and peat or CPS-amended soils and sediment slurries, but not in the mineral soil or sediment slurries. Hexazinone was chemically dissipated best in the peat amended mineral soil and sediment slurries. In contrast, dichlobenil chemically dissipated in the mineral soil and sediment slurries. The dissipation product 2,6-dichlorobenzamide (BAM) concentrations were lowest in the mineral soil, while dissipation was generally poor regardless of plant-derived OM, only algal agar enhanced its chemical dissipation. Based on sterilized counterparts, only terbutryn appeared to be microbially degraded in the organic soil, i.e. chemical dissipation of pesticides would appear to be utmost important, and could be the first response in the natural cleansing capacity of the environment, during which microbial degradation evolves. Consistent with compound-specific dissipation in the mineral or organic environments, long-term concentrations of pentachloroaniline and hexachlorobenzene were lowest in the mineral-rich soils, while concentrations of dichlorodiphenyltrichloroethane (DTT) and metabolites were lowest in the organic soils of old market gardens. OM amendments changed pesticide dissipation in the mineral soil towards that observed in the organic soil; that is OM accelerated, slowed down or stopped dissipation.